WHITE RATS’ THYROID GLAND MORPHOLOGICAL CHANGES THROUGHOUT THE EXPERIMENTAL THERMAL INJURY IN CONDITIONS OF LACTOPROTEIN WITH SORBITOL HYPEROSMOLAR SOLUTIONS ADMINISTRATION - Tiron, O.I.; Herasimenko, O.S.; Nikogosyan, L.R.; Nescoromna, N.V.; Merlich, S.V.; Rusalkina, L.G.; Vastyanov, M.R. (World of Medicine and Biology, 2023)
The purpose of the study was to establish the animal’s thyroid gland histological changes after thermal skin injury in conditions of lactoprotein with sorbitol hyperosmolar colloid solution using. One day after the skin thermal injury and the abovenamed solution application one could reveal changes in the thyroid gland of animals manifested as the perivascular and interstitial edema, stasis in small vessels and the presence of a large number of resorption vacuoles inside the follicles’ colloid. Three days after the skin thermal burn and the lactoprotein with sorbitol infusion the data did not show any progression of edematous phenomena neither around the blood vessels of the organ nor in the stromal connective tissue. On the 7th and the 14th days of a trial one could register the signs of thyroid gland capsule thickening and densification. Throughout the late stages of the trial there were no signs of the inflammatory process in the thyroid gland connective tissue. A moderate organs’ vascular blood filling was observed on the sections stained with hematoxylin and eosin. Thus, the use of a hyperosmolar colloid lactoprotein with sorbitol solution as a corrective substance in experimental skin thermal injury reveals positive influence on the thyroid gland morphological state. The first signs of intraglandular environment recovery began to be registered from the 7th day of the trial, and the maximally expressed protective effect of lactoprotein with sorbitol hyperosmolar colloidal solution administration was observed from the 21st day till the end of the experiment.